2017
DOI: 10.1097/md.0000000000007952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microRNA-21 on apoptosis by regulating the expression of PTEN in diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is an aggressive malignancy and the most common subtype of non-Hodgkin lymphoma in China. However, many cases still remain biologically and clinically heterogeneous, indicating that the DLBCL mechanism remains unclear. MicroRNAs (miRNAs) are critically responsible for lymphomagenesis. We found that plasma miR-21 level was significantly higher in B-cell lymphoma. However, the exact contribution of miR-21 in DLBCL remains unknown.To determine the function and mechanism of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 26 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…Twenty-one studies analyzed the expression of miRNAs by comparing DLBCL cases vs healthy controls [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. These 21 studies provided a total of 140 differentially expressed microRNAs in DLBCL patients compared with healthy control individuals as shown in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies analyzed the expression of miRNAs by comparing DLBCL cases vs healthy controls [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. These 21 studies provided a total of 140 differentially expressed microRNAs in DLBCL patients compared with healthy control individuals as shown in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have investigated miRNA profiles in diffuse large B-cell lymphoma (DLBCL) [41][42][43][44][45][46]. miR-181a-5p is reported to be upregulated in peripheral blood of acute lymphoblastic leukemia compared with normal peripheral blood mononuclear cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…This is a proteasome inhibitor used to suppress Diffuse large B-cell lymphoma (DLBCL) progression [ 223 , 224 , 225 ]. DLBCL is the most frequent non-Hodgkin lymphoma, showing variable clinical presentations as well as variable therapy responses [ 226 , 227 , 228 ]. In vitro studies on DLBCL CRL-2630 cells showed that BTZ treatment significantly inhibited the proliferation of DLBCL CRL-2630 cells [ 229 ].…”
Section: Hmga Proteins As Targetable Markersmentioning
confidence: 99%